Cellular activation pathways and interaction networks in vascularized composite allotransplantation - Knoedler, Leonard; Knoedler, Samuel; Panayi, Adriana C.; Lee, Catherine A. A.; Sadigh, Sam; Huelsboemer, Lioba; Stoegner, Viola A.; Schroeter, Andreas; Kern, Barbara; Mookerjee, Vikram; Lian, Christine G.; Tullius, Stefan G.; et al. (Frontiers in immunology, 2023)
Vascularized composite allotransplantation (VCA) is an evolving field of reconstructive surgery that has revolutionized the treatment of patients with devastating injuries, including those with limb losses or facial disfigurement. The transplanted units are typically comprised of different tissue types, including skin, mucosa, blood and lymphatic vasculature, muscle, and bone. It is widely accepted that the antigenicity of some VCA components, such as skin, is particularly potent in eliciting a strong recipient rejection response following transplantation. The fine line between tolerance and rejection of the graft is orchestrated by different cell types, including both donor and recipient-derived lymphocytes, macrophages, and other immune and donor-derived tissue cells (e.g., endothelium). Here, we delineate the role of different cell and tissue types during VCA rejection. Rejection of VCA grafts and the necessity of life-long multidrug immunosuppression remains one of the major challenges in this field. This review sheds light on recent developments in decoding the cellular signature of graft rejection in VCA and how these may, ultimately, influence the clinical management of VCA patients by way of novel therapies that target specific cellular processes.
Gesehen am 21.11.2023